Experimental Techniques to Assess Coral Physiology in situ Under Global and Local Stressors: Current Approaches and Novel Insights - Dellisanti, Walter; Chung, Jeffery T. H.; Chow, Cher F. Y.; Wu, Jiajun; Wells, Mark L.; Chan, Leo L. (Frontiers in Physiology, 2021)
Coral reefs are declining worldwide due to global changes in the marine environment. The increasing frequency of massive bleaching events in the tropics is highlighting the need to better understand the stages of coral physiological responses to extreme conditions. Moreover, like many other coastal regions, coral reef ecosystems are facing additional localized anthropogenic issues such as nutrient loading, increased turbidity, and coastal development. Different strategies have been developed to measure the health status of a damaged reef, ranging from the resolution of individual polyps to an entire coral community, but techniques for measuring coral physiology in situ are not yet widely implemented. For instance, while there are many studies of the coral holo-biont response in single or limited-number multiple stressor experiments, they provide only partial insights into metabolic performance under more complex temporally and spatially variable natural conditions. Here, we discuss the current status of coral reefs and their global and local stressors in the context of experimental techniques that measure core processes in coral metabolism (respiration, photosynthesis, and biocalcification) in situ, and their role in indicating the health status of colonies and communities. We highlight the need to improve the capability of in situ studies in order to better understand the resilience and stress response of corals under multiple global and local scale stressors.